Conservation Policy of Visual Quality in Connecting Area Between Historical Areas - Garudea Garudea; Bambang Soemardiono; Didit Novianto (Pusbindiklatren Bappenas, 2024)
Alun-alun Contong, a historical area in Surabaya, connects popular historical areas via a tram line. Today, it features commercial buildings from the Dutch East Indies era, which is dominated by contemporary style. Therefore, historical appearances have become degraded and disconnected from their surrounding areas. Based on the case study, this research tries to construct specific historical conservation policies on connecting areas that have not been discussed before. The mixed method involves several tactics that involve two phases: assessment of the building facade element and serial vision analysis as an internal and external identification. The results show the visual quality condition and potential of an area between two historical areas as a modality of the Alun-alun Contong conservation policy. The research findings enable conservation policies to use this method at other locations to improve or restore connectivity, strengthen visual quality, and ensure the sustainability of the entire urban heritage area.